Exploring the charge storage ability of the spinel-type high entropy oxide (MnFeCoNiZn)3O4 nanoparticles for supercapacitor applications - Arun S R; George Jacob (Chemical Engineering Journal Advances)
High entropy materials have grabbed more attention in recent years on account of their unique crystal structure, large compositional design space, and complex chemistry enabling the enormous and unexplored properties in the different fields. Among the entropy-stabilized materials, high entropy oxide nanoparticles (HEO NPs) have attracted the scientific community owing to their superior energy storage applications. This research anticipates an approach for unleashing the charge storage properties of HEO NPs for supercapacitor applications. The spinel-type (MnFeCoNiZn)3O4 HEO NPs were prepared by the solution combustion method. This (MnFeCoNiZn)3O4 HEO NPs electrode exhibited 288.7 Fg-1 (3 Ag-1) of specific capacitance (Csp). It maintained a 52% rate capability from 3 to 30 Ag-1. Furthermore, after a cyclic stability test for 5000 cycles, this (MnFeCoNiZn)3O4 HEO NPs maintained 50% capacity retention at 10 Ag-1. Additionally, an asymmetric supercapacitor (ASC) was constructed of ((MnFeCoNiZn)3O4 HEO NPs // activated carbon (AC)) which exhibited a 1.5 V voltage window. It delivered a good energy density of 7.9 Whkg-1 with a power density of 746 WKg-1. This research has paved the way for preparing the HEO NPs by simple synthesizing methods and exploration of high entropy materials in the field of supercapacitors.